Characterization of the Effects of a Six-Month Dancing as Approach for Successful Aging. (17th June 2019) - Vaccaro, Maria Grazia; Izzo, Giulia; Ilacqua, Alessandro; Migliaccio, Silvia; Baldari, Carlo; Guidetti, Laura; Lenzi, Andrea; Quattrone, Aldo; Aversa, Antonio; Emerenziani, Gian Pietro
Abstract : Aging is accompanied by a decline in multiple domains. Positive effects of dance practice on several health issues have been evaluated in young adults, while the effects of regular social dance practice on physical fitness, sexual health, and cognitive functions have not been studied yet in older experienced dancers. Thus, the aim of this study has been to investigate whether a 6-month social dance practice might influence fitness performance, sexual health, and specific cognitive functions and/or mood characteristics in older experienced dancers. Thirty experienced dancers (age: 71.2±5.1 years, 18 females/12 males) were enrolled from the dance school "NonSoloLiscio" of Catanzaro. Body composition, physical fitness, sexual health, and cognitive functions were assessed before (T0) and after (T6) intervention. After 6 months of dance practice, percent of fat mass (%FM) significantly decreased (p<0.01), while fat-free mass (FFM) significantly increased (p<0.01) in both genders. Moreover, significant main effects of time on physical fitness tests, such as chair stand test (CST) (p<0.01), gait speed (p<0.05), and timed up and go (p<0.05), were found. Sexual health was significantly higher in males than in females at T0 and no significant effects of dance on subjects' sexual health were found. Interestingly, trait of anxiety significant decreased (p<0.05) and perception of retrospective memory significantly increased (p=0.05) after training independently of gender. Our preliminary results suggest that, even in older intermediate-level dancer, the practice of social dance might positively influence body composition and also increase fitness performance, memory functions, and anxiety. In contrast, no effects on sexual health were observed after 6 months of dancing.